PENGARUH PENERAPAN KOMUNIKASI TERAPUETIK TERHADAP PENURUNAN INTENSITAS NYERI PERSALINAN KALA 1 DI BPM SANITA HUTABARAT KEC. PANCUR BATU TAHUN 2021 - Erlina Hayati; Febry Ichwan Butsi (Jurnal Ilmiah Ilmu Komunikasi Communique, 2021)
Pain is a normal thing and is an inseparable part of childbirth. Labor pain occurs due to uterine contractions that cause cervical dilatation and thinning and uterine ischemia, namely a decrease in blood flow so that local oxygen has a deficit due to myometrial contractions. Discomfort in the form of pain during labor is subjective to each mother in labor. This type of research is a quasiexperimental research with the design used is pretest and posttest with control group design, which is done by dividing the group. The purpose of this study was to determine the effect of applying therapeutic communication on reducing the intensity of labor pain in the first stage at BPM Sanita Hutabarat in 2021. This research was conducted at BPM Sanita Hutabarat JL HM. Puna Sembiring no. 58, Pancur Batu District, North Sumatra Province. The sampling technique used is total sampling. The sample in this study amounted to 25 respondents. From the research, it was found that the data on the intensity of labor pain in the first stage of labor in the control group before (pretest) was 0.111 and the intensity of labor pain in the first stage after (post test) was 0.217. While the intensity of labor pain in the first stage of the experimental group before (pretest) was 0.001 and the intensity of labor pain in the first stage after (post-test) was given experimentally 0.034. This shows that the data on the intensity of labor pain in the first stage before and after the application of therapeutic communication in the control group and the intervention group were not normally distributed because they had a significance value of <0.05.